An effective intrusion detection approach using SVM with naïve Bayes feature embedding. Issue 103 (April 2021) - Gu, Jie; Lu, Shan
Abstract: Network security has become increasingly important in recent decades, while intrusion detection system plays a critical role in protecting it. Various machine learning techniques have been applied to intrusion detection, among which SVM has been considered as an effective method. However, existing studies rarely take the data quality into consideration, which is essential for constructing a well-performed intrusion detection system beyond machine learning techniques. In this paper, we propose an effective intrusion detection framework based on SVM with naïve Bayes feature embedding. Specifically, the naïve Bayes feature transformation technique is implemented on the original features to generate new data with high quality; then, an SVM classifier is trained using the transformed data to build the intrusion detection model. Experiments on multiple datasets in intrusion detection domain validate that the proposed detection method can achieve good and robust performances, with 93.75% accuracy on UNSW-NB15 dataset, 98.92% accuracy on CICIDS2017 dataset, 99.35% accuracy on NSL-KDD dataset and 98.58% accuracy on Kyoto 2006+ dataset. Furthermore, our method possesses huge advantages in terms of accuracy, detection rate and false alarm rate when compared to other methods.